2019
DOI: 10.1103/physrevc.99.024914
|View full text |Cite
|
Sign up to set email alerts
|

Probing hot and dense nuclear matter with K*, K¯* vector mesons

Abstract: We investigate the possibility of probing the hot and dense nuclear matter -created in relativistic heavy-ion collisions (HIC) -with strange vector mesons (K * ,K * ). Our analysis is based on the non-equilibrium Parton-Hadron-String Dynamics (PHSD) transport approach which incorporates partonic and hadronic degrees-of-freedom and describes the full dynamics of HIC on a microscopic level -starting from the primary nucleon-nucleon collisions to the formation of the strongly interacting Quark-Gluon-Plasma (QGP),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…An example of such studies performed for K * (892) 0 can be found in Ref. [34]. Similar studies are not yet available for ρ(770) 0 .…”
Section: Introductionmentioning
confidence: 99%
“…An example of such studies performed for K * (892) 0 can be found in Ref. [34]. Similar studies are not yet available for ρ(770) 0 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we expect the mass shift to first approximation to behave qualitatively like a relativistic Breit-Wigner distribution (BW) multiplied by the thermal weight of each resonance (often called phase-space factor [PS]) (Fachini et al 2007;Ilner et al 2019). In the case of the Δ(1232), which is a very short-lived resonance, this effect is even stronger because the Δ(1232) decays quickly and is regenerated many times before its final detectable decay occurs.…”
Section: Mass Distributionmentioning
confidence: 99%
“…This implies two features, namely, that (a) the local temperature of the system decides where the Δ(1232) is going to be populated in its invariant mass distribution and (b) the mass distribution can possibly be used to determine the temperature of the system at the kinetic freeze‐out surface. Hence, we expect the mass shift to first approximation to behave qualitatively like a relativistic Breit‐Wigner distribution (BW) multiplied by the thermal weight of each resonance (often called phase‐space factor [PS]) (Fachini et al ; Ilner et al ). That is, PmΔpBWmΔmΔ0ΓΔ0×PSmΔpT, with BWmΔmΔ0ΓΔ0ΓmΔ()mΔ2mΔ02+()ΓmΔ2, and PSmΔpTmΔmΔ2+p2expmΔ2+p2T. …”
Section: Introductionmentioning
confidence: 99%
“…Very recently, K and K Ã formation in relativistic heavy-ion collisions has been investigated in the context of the Parton-Hadron-String dynamics (PHSD) transport approach [38,39], which considers the in-medium effects in the K andK Ã states through the modification of their spectral properties during the propagation through the medium. The authors conclude that final state interactions (in the hadron gas) contribute to reduce the ratio K Ã /K, corroborating the findings of Ref.…”
Section: Fig 7 Exchange Of the K ãmentioning
confidence: 99%